Association of Cardiac Abnormalities to the Frail Phenotype in Cirrhotic Patients on the Waitlist: From the Functional Assessment in Liver Transplantation Study. Issue 3 (March 2018) - Puchades, Lorena; Chau, Stephanie; Dodson, John A.; Mohamad, Yara; Mustain, Rachel; Lebsack, Adrienne; Aguilera, Victoria; Prieto, Martin; Lai, Jennifer C.
Abstract : Background: Frailty is a syndrome of decreased physiologic reserve that results from compromise of multiple physiologic systems including cardiovascular system. We aimed to determine the association between the frail phenotype and cardiac abnormalities in liver transplant (LT) candidates through evaluation of transthoracic echocardiography (TTE) indices. Methods: Included were consecutive outpatients listed for LT who underwent a frailty assessment from January 1, 2014, to June 30, 2016 (using the Liver Frailty Index) and a 2-dimensional/Doppler TTE examination. Patients were categorized as robust, intermediate frail, or frail by the Liver Frailty Index based on scores of less than 3.2, between 3.2 and 4.5, or 4.5 or greater. Linear regression assessed associations between the Liver Frailty Index and TTE indices. Results: Of 335 patients, 19% were robust, 65% intermediate frail, and 16% frail. TTE indices of left atrial (LA) dilatation differed significantly by frailty status: median LA dimension ( P = 0.03), LA volume index (LAVI mL/m 2 ; P < 0.001) and %LAVI > 34 mL/m 2 ( P = 0.001). In linear regression adjusted for age, sex, hypertension, and diabetes, the Liver Frailty Index was positively associated with LA dimension (coeff, 0.20; 95% confidence interval [CI], 0.07-0.34), LAVI mL/m 2 (coeff, 0.01; 95% CI, 0.005-0.02), ejection fraction (coeff, 1.59; 95% CI, 0.32-2.85), and pulmonary artery systolic pressure (coeff, 0.01; 95% CI, 0.003-0.02), and negatively associated with LV hypertrophy (coeff, −0.22; 95% CI, −0.37 to −0.06). Conclusions: In LT candidates, frailty is associated with cardiac structural and functional changes, independent of known risk factors. Our study provides evidence to support that measures of frailty in cirrhotic patients encompass abnormalities of the cardiovascular system and may inform assessments of cardiovascular reserve in this population. Abstract : The authors report the association between the frail phenotype and cardiac abnormalities in liver transplantation candidates through the evaluation of transthoracic echocardiography (TTE) indices. They find that frailty is associated with cardiac structural and functional changes, independent of known risk factors.